An analysis of conjunctive relations in the translation of Animal Farm from English to Hausa / Muhammad Sulaiman Abdullahi - Muhammad Sulaiman, Abdullahi (2015)
The aim of this study is to find out what kind of shifts exist in the translation of inter-sentential conjunctive relations in the novel, Animal Farm, from English to Hausa based on Catford‘s (1965) notion of shifts in translation. The two novels used as the sources of data for this study were the source text in English, Animal Farm and its target language translation in Hausa, Gandun Dabbobi. Two hundred and fifty-two sentences containing inter-sentential conjunctive relations were extracted from each text, making the total number of five hundred and four sentences from both texts. Halliday and Hasan‘s (1976) Table of Conjunctive Relations was used to identify the different conjunctive relations. Equally, the effects of the shifts on the target language were also studied and explained in the data. This was done using Nida‘s (1964) theory of formal and functional equivalence. Thirty different forms of shifts were found under three out of the five major classifications of shifts according to Catford (1965). These included seven forms of structure shifts, seven forms of unit shifts, with class shifts being the most common with sixteen different forms. Furthermore, this study also revealed that all the categories of conjunctive relations: additives, adversatives, causal and temporal were shifted in the translation but their shifts differed between one class of conjunctions to another. The findings also show that, apart from shifts, other strategies of translation such as maintaining formal correspondence and omissions were also found along with shifts in the translation of inter-sentential conjunctive relations from English to Hausa.